2017
DOI: 10.1186/s13034-017-0188-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adolescents’ mental health problems in Saudi Arabia: findings from the Jeeluna® national study

Abstract: BackgroundDepression and anxiety among adolescents require further attention as they have profound harmful implications on several aspects of adolescents’ wellbeing and can be associated with life threatening risk behaviors such as suicide.ObjectiveTo examine the underlying risk factors for feeling so sad or hopeless and for feeling worried among adolescents in Saudi Arabia.MethodsData from Jeeluna® national survey was used. A cross-sectional, multi-stage, stratified, cluster random sampling technique was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 39 publications
3
12
0
Order By: Relevance
“…36,37 In India, Jaisoorya et al, 38 also reported increased depression with older adolescents. The Jeeluna national study found that feeling deeply sad or hopeless and worried was significantly more prevalent among females and older adolescents )p<0.0001(, 39 which is consistent with the findings of this study, where depression among female adolescents was more prevalent than those among males.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…36,37 In India, Jaisoorya et al, 38 also reported increased depression with older adolescents. The Jeeluna national study found that feeling deeply sad or hopeless and worried was significantly more prevalent among females and older adolescents )p<0.0001(, 39 which is consistent with the findings of this study, where depression among female adolescents was more prevalent than those among males.…”
Section: Resultssupporting
confidence: 91%
“…11 The Jeeluna national survey found that poor relationships with parents, negative body image, and chronic illness were significantly associated with feeling sad or hopeless. 39 Some researchers support the argument that Internet addiction can be associated with depression, 41 which aligns with this study results. The results show that with increased daily use of the Internet, there is an increase in the prevalence of depression.…”
Section: Resultssupporting
confidence: 87%
“…According to our study, the presence of physical health conditions was a significant factor associated with the prevalence of anxiety and depression. Poor physical health of adolescents has been often acknowledged as a risk factor of both depression and anxiety in previous studies as well (Abou Abbas & AlBuhairan, 2017;Ghandour et al, 2019;Wahid et al, 2021). Jordanian adolescent females exhibiting poor physical health should be identified as an at-risk group and given priority and directed for depression and anxiety screening, referral, and management if needed.…”
Section: Discussionmentioning
confidence: 99%
“…There are several factors that increase adolescent vulnerability to depression and anxiety including being older (Ghandour et al, 2019;Mohammadi et al, 2020;Sandal et al, 2017;Tang et al, 2019), having poorer physical health (Abou Abbas & AlBuhairan, 2017;Ghandour et al, 2019), higher academic pressure (Sharma & Choulagai, 2019), and poor academic performance (Latiff et al, 2016;Tang et al, 2019). Additionally, female adolescents are particularly vulnerable to mental health disorders.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,8,9,10 Among other indicators addressing prevalent health problems among nationally representative samples of adolescents, 14% and 6.7%, respectively, were found to have symptoms suggestive of depression and anxiety. 11 In addition, a Study in Hail region of Saudi Arabia showed that despite the favorable attitude of teachers within the targeted population toward students with mental health issues, they reported having limited information about most aspects needed for early detection dealing with and referral for specialized mental health counseling available in their school and community. 12 Most teens spend most of their waking time in school with their teachers more than anyone, making schools the prime setting for early detection and intervention strategy for mental health problems among children and adolescents.…”
mentioning
confidence: 99%